Late Pleistocene to Holocene alluvial tableland formation in an intra-mountainous basin in a tectonically active mountain belt ― A case study in the Puli Basin, central Taiwan. (15th January 2016) - Tseng, Chia-Han; Lüthgens, Christopher; Tsukamoto, Sumiko; Reimann, Tony; Frechen, Manfred; Böse, Margot
Abstract: The morphology in Taiwan is a product of high tectonic activity at the convergent margin and East Asian monsoon climate. Tablelands are prominent geomorphic features in the Puli Basin in central Taiwan. These tablelands provide an archive to understand links between past climatic evolution and tectonic events resulting in the formation of the present-day landforms. To establish a geochronological framework for the alluvium underlying the tablelands in the Puli Basin, optically stimulated luminescence dating was applied to obtain burial ages. The numerical data indicate an accumulation phase of alluvial fans in the Late Pleistocene to Early Holocene transition. The study area in the Taomi River catchment, an obvious longer precursor of the Taomi River, originating from west of the Yuchih Basin, transported the sediments forming the present-day southern tablelands. During the Pleistocene–Holocene transition, the climate changed to wetter and warmer conditions, so that slope processes might have changed and an increasing transport in the fluvial system was stimulated. Fluvial and fan terraces in other river catchments in Taiwan also indicate a period of increased fluvial transport and deposition. A geomorphic evolution model in the Puli Basin is reconstructed on the basis of the chronological framework and of sedimentological features. Fluvial processes controlled by climatic change and accompanied by tectonic activities have created the diverse topography in the Puli Basin. Highlights: OSL chronology on alluvial fan material (gravel layer). Alluvial fan/tableland stratigraphy from the Late Pleistocene to the Holocene. Sedimentological analyses of alluvial fan sediments. Geomorphic evolution within tectonically intra-mountainous basins. Introduction of an evolutionary model of tablealnd development in a tectonically active mountain belt.